ANALISIS KINERJA KEUANGAN BPJS KETENAGAKERJAAN - Layuk, Liliani Randa (EKONOMIA, 2019)
Liliani Randa Layuk, Financial performance analysis of institution of social Security employment supervised by Mrs. Elfreda Aplonia Lau as mentor I and supervised by Mr. Heryanto as mentor II.The purposes of the research are is to know and analyze the financial performance Institution of Social Security employment was measured Â by liquidity and solvability period 2014 until 2016.The analysis tool was used in this research is liquidity ratio consisting of current ratio and cash ratio, solvency ratio consisting of total debt to total assets ratio and total debt to equity ratio.The results shows that the financial performance Institution of Social Security employment measured by the liquidity ratio Current ratio increased in 2015 by 16.87% and was decreased in 2016 of 279.78%. Cash ratio decreased in 2015 by 55.11% and in 2016 also decreased by 5.77%. Furthermore, the total solvency ratio of debt to total assets ratio in 2015 decreased by 0.39% but in 2016 has increased by 2.42%. Total debt to equity ratio in 2015 was decreased by 3.95% and increased by 2016 by 3.48%. Overall, the financial performance of Institution of Social Security employment viewed from the liquidity ratio (current ratio) in 2014 to 2016 shows the result fluktuate so that the hypothesis is rejected.The ratio of liquidity (cash ratio) in 2014 until 2016 shows the result decreased so the hypothesis is accepted.While the financial performance Institution of Social Security employment reviewed from the ratio of solvability (total debt to total assets ratio) in 2014 to 2016 also fluktuate so the hypothesis rejected.